Resistance Profile of Extended Spectrum Beta Lactamase-Producing Escherichia coli Bacteria using Vitek® 2 Compact Method - Freshinta Jellia Wibisono; Bambang Sumiarto; Tri Untari; Mustofa Helmi Effendi; Dian Ayu Permatasari; Adiana Mutamsari Witaningrum (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
This study aimed to determine the resistance profile and the nature of multidrug resistance in Extended Spectrum Beta Lactamase (ESBL)-producing Escherichia coli (E.coli) against several classes of antibiotics. Positive isolates of ESBL-producing E.coli were tested for antibiotic sensitivity using the VITEK® 2 compact method which then analyzed automatically. The results showed an antibiotic resistance profile against ESBL-producing E.coli showed the highest level of antibiotics in beta lactam, amoxicillin, ampicillin, cefazolin, cefotaxime, and ceftriaxone at 100%. Subsequent results found a relatively high level of resistance in the antibiotics aztreonam (86.36%), trimethoprim/sulfamethoxazole (77.27%), gentamicin (72.73%), and ciprofloxacin (68.18%). Antibiotics from carbapenem groups such as ertapenem and memenem, and antibiotics from the aminoglycosides (amicasin) and tigecycline groups of tetracycline still showed a high sensitivity level of 100%. The most common resistance patterns found in ESBL-producing E.coli isolates are AM/AMP/KZ/CTX/CRO/ATM/GM/CIP as much as 22.73%, and AM/AMP/KZ/CTX/CRO/ATM/GM/CIP/SXT patterns of 18.2%. The results of multi-class antibiotic resistance showed that 86.36% had multidrug resistance. The highest multidrug resistance pattern in ESBL-producing E.coli occurred with a BL/AG/Q/SP pattern of 50%. Other patterns of multidrug resistance in ESBL-producing E.coli that can be found in this study are, the BL/AG/Q/SP pattern is 18.20%, the BL/AG/Q/SP pattern is 13.64%, and the BL/AG/Q pattern is 4.55%. The high profile of resistance and the nature of multidrug resistance in ESBL-producing E.coli has the potential to spread these resistant genes, thus risking the use of antibiotics as a public health therapy and animal health, therefore further evaluation and control are needed.